Acute Exacerbation of Symptoms After Lumbar Decompression Surgery: An Analysis Readmissions and Reoperations in 81 365 Patients. (1st September 2019) - Samuel, Andre; Vaishnav, Avani; Mcanany, Steven; Iyer, Sravisht; Albert, Todd; Gang, Catherine; Qureshi, Sheeraz
Abstract: INTRODUCTION: While lumbar spine decompression is a common surgical procedure, acute readmission or reoperation for exacerbation of symptoms is a rare occurrence that has not been extensively studied. METHODS: A retrospective review was conducted of a national cohort of patients who underwent lumbar spine decompression surgery between 2013 and 2016. Readmission within 30 d postoperatively, due to exacerbation of back pain, leg pain, or neurological deficits were identified. Reoperations within 30 d for revision spinal decompression or fusion were also measured. Multivariate logistic regression was utilized to determine preoperative patient and surgical factors associated with 30-d readmissions or reoperations. RESULTS: In all 40% patients underwent a laminectomy or bilateral decompression and 62% underwent a foraminotomy or unilateral decompression. A total of 3188 patients (3.9%) were readmitted within 30-d postoperatively due to exacerbation of back pain, leg pain, or neurological deficits. A total of 1967 patients (2.4%) underwent reoperation for revision spinal decompression or fusion within 30-d postoperatively. Revision decompression (OR: 2.0, P = .01), additional levels of foraminotomy/unilateral decompression levels (OR: 1.3, 1.5, and 2.5 for 1, 2, and 3+ levels, P = .05), microscopic laminectomy (OR: 1.5, P = .04), and female sex (odds ratios [OR]: 1.2, P = .01) were associated with increased likelihood for readmission. Revision decompression surgery (OR: 2.0) and additional foraminotomy/unilateral decompression levels (OR: 1.9, 1.8, and 2.3 for 1, 2, and 3 + levels, P = .05) were associated with an increased likelihood of reoperation. CONCLUSION: While acute readmission or reoperation for symptom exacerbation after lumbar decompression is a rare occurrence, incidence of exacerbation increases with revision decompression surgery and multilevel foraminotomies/unilateral decompression.